A transformação do mercado de trabalho: sugestões para melhorar as condições do teletrabalho no Brasil - Lucca, Nakyta Nara (2024)
Telecommuting, a form of flexible work inherent in the contemporary world, owes its feasibility to the microelectronics revolution. Understanding and defining telecommuting is the starting point for all stakeholders in the labor scenario to implement and maintain best practices, ensuring appropriate conditions and relationships for both workers and employers. The ability to perform tasks from any location, not strictly confined to the physical workplace, became an emphasized reality in 2020 with the outbreak of the Covid-19 pandemic. Since then, there has been progress in internal regulations within companies, countries and international organizations; however, not all of them have comprehensively and fully addressed the various factors and impacts that telecommuting may entail, especially on the worker’s life. It is considered that not all actores in the labor scenario are prepared to adopt the telecommuting modality, either due to the nature of their roles or the need for organizational skills different from those professionals are currently familiar with. This study aims to explore, analyse, and suggest possibilities for improvements in the implementation and maintenance of telecommuting in Brazil, while presenting the benefits and challenges that this modality introduces into the labor scenario. Through concrete examples, the goal is to provide applicable guidelines in different contexts, countries, organizations and companies, with the purpose of ensuring the rights already achieved by workers